Cardiac Failure after Liver Transplantation Requiring a Biventricular Assist Device. (9th November 2014) - Jermyn, Rita; Soe, Eiei; D'Alessandro, David; Shin, Julia; Jakobleff, William; Schwartz, Daniel; Kinkhabwala, Milan; Gaglio, Paul J.
Abstract : Increased hepatic iron load in extrahepatic organs of cirrhotic patients with and without hereditary hemochromatosis portends a poorer long term prognosis after liver transplant. Hepatic as well as nonhepatic iron overload is associated with increased infectious and postoperative complications, including cardiac dysfunction. In this case report, we describe a cirrhotic patient with alpha 1 antitrypsin deficiency and nonhereditary hemochromatosis (non-HFE) that developed cardiogenic shock requiring mechanical circulatory support for twenty days after liver transplant. Upon further investigation, she was found to have significant iron deposition in both the liver and heart biopsies. Her heart regained complete and sustained recovery following ten days of mechanical biventricular support. This case highlights the importance of preoperatively recognizing extrahepatic iron deposition in patients referred for liver transplantation irrespective of etiology of liver disease as this may prevent postoperative complications.